2019
DOI: 10.1097/rhu.0000000000001234
|View full text |Cite
|
Sign up to set email alerts
|

Anti–Jo-1 Syndrome Often Misdiagnosed as Rheumatoid Arthritis (for Many Years)

Abstract: Background: Antisynthetase syndrome is characterized by a triad of myositis, arthritis, and interstitial lung disease. Anti-Jo-1 is the most common associated autoantibody. This study planned to look at the presentation of anti-Jo-1 antisynthetase syndrome in a single Indian center. Methods and Materials:This was a medical records review singlecenter study that included patients with anti-Jo-1 antisynthetase syndrome over 10 years.Results: This study included 27 patients with anti-Jo-1 antisynthetase syndrome,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…The prevalence of ILD in most cohorts, including ours, was ∼75% [ 10 , 11 , 16 ]. Non-specific interstitial pneumonia, as in other studies, was the commonest pattern present on high-resolution CT in our study [ 9 , 13 , 16 , 17 ]. Although the two RP-ILD cases in our cohort were anti-Jo-1 positive, Shi et al [ 9 ] reported a significant association with anti-PL-7 antibodies and mortality of ∼9%.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The prevalence of ILD in most cohorts, including ours, was ∼75% [ 10 , 11 , 16 ]. Non-specific interstitial pneumonia, as in other studies, was the commonest pattern present on high-resolution CT in our study [ 9 , 13 , 16 , 17 ]. Although the two RP-ILD cases in our cohort were anti-Jo-1 positive, Shi et al [ 9 ] reported a significant association with anti-PL-7 antibodies and mortality of ∼9%.…”
Section: Discussionsupporting
confidence: 88%
“…Rojas-Serrano et al [ 12 ] reported 43 Mexican ASS patients, and Shi et al [ 9 ] described 124 Chinese patients with 18 and 22 years of follow-up, respectively. The cohorts that focused on anti-Jo-1-positive patients were the European American AENEAS group (58 patients), the cohort described by Kumar et al from India (27 patients), and the Spanish group by Trallero-Araguás et al (148 patients) [ 1 , 13 , 14 ]. The study by Srivastava et al [ 15 ] on the prevalence of myositis-specific and -associated antibodies in a North Indian population reported 29 ASS patients, of whom 14 were Jo-1 positive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hervier and Lambert et al reported an interesting rare case of overlap syndrome with PL-7 ASS, Sjogren's, systemic lupus erythematosus and RA with evolving symptoms over time. 8,[13][14][15] Anti-synthetase syndrome has often been reported in overlap with polymyositis, dermatomyositis, systemic sclerosis, Sjogren's and RA.…”
Section: Discussionmentioning
confidence: 99%